Nigerian indigenous hens show more discomfort-related behavior with visual separation than physical separation from their chicks: An exploratory study - Iyasere, Oluwaseun S.; Olajumoke, Olawale P.; Durosaro, Samuel O.; Oke, O. E.; Famosaya, Oluwabukunmi O.; Oliyide, Kolade M.; Oyeniran, Victor J. (Frontiers in Veterinary Science, 2022)
The Nigerian indigenous hens exhibit their full natural behavior repertoires, including maternal care. The strong maternal bond between the hen and her chicks is established prior to hatching. Maternal care in chickens is essential for both exotic and indigenous chickens. This study compared the behaviors of six hen-chick pairs in a physical (PHY) and visual (VIS) separation test for 10 minutes. All the six hen-chick pairs were subjected to PHY separation on the 8th day of post-hatch and a VIS separation on the 12th day of post-hatch. The PHY separation involved the use of a wire mesh to separate the hen from her chicks, while the VIS separation involved the use of a trampoline to separate the hen from her chicks. The hen’s behavior was recorded during the 10-minute separation period. Behaviors recorded included sitting, body shaking, pecking, movements towards the chicks, jumping, pacing, defecation, movements away from the chicks, and preening. We further grouped these nine behaviors into two categories: discomfort-related (pacing, movement towards chicks, body shaking, defecation, and jumping) and comfort-related (sitting, pecking, preening, and movement away from the chicks) behaviors. Before and after each separation, the hens were gently restrained, and a drop of blood was sampled from the wing vein to determine the blood glucose level. Their heart rate and eye temperature were also measured. A two-related samples test (Wilcoxon) was used to compare the behavior of the hens when subjected to the PHY and VIS separation. Eight out of the nine behaviors monitored did not differ between the separation types. However, the frequency of pacing by the hens was greater (z = -2.201, P = 0.028) in the VIS than in PHY separation. Also, discomfort-related behavior was greater (t(5) = -2.717, P= 0.042) during VIS than PHY separation. Comfort-related behavior did not differ between the separation types. The change in eye temperature, heart rate, and blood glucose was similar in the two separation types. In conclusion, Nigerian indigenous hens displayed more discomfort-related behavior to VIS separation from their chicks, but this was not associated with physiological responses indicative of stress.